'My Husband is My Key to Paradise.' Attitudes of Muslims in Indonesia and Norway to Spousal Roles and Wife-Beating. Issue 2 (3rd April 2018) - Eidhamar, Levi Geir
ABSTRACT: This article explores the influence of religious factors and values held by local societies, when Muslims develop their personal attitudes and perceived religious norms regarding spousal roles and wife-beating. It is based on qualitative interviews with 59 Muslims in Indonesia ( N  = 35) and Norway ( N  = 24). In addition, relevant Indonesian and Norwegian Muslim literature and web pages are examined. According to most Indonesian respondents, Islamic norms prescribe male leadership and allow the husband to beat a disobedient wife. This was regarded as crucial for the wife's destiny after death. According to most Norwegian respondents, Islamic norms promote gender equality and oppose wife-beating. The sharp contrast between the perceived religious norms of Indonesian and Norwegian respondents may be caused by dissimilar cultural values in the two countries – values that influenced personal attitudes and thus the horizon of understanding where religion and authoritative text were interpreted. The reasoning of the respondents also sheds light on the importance of specific sacred texts when religious norms were developed individually. From a psychological point of view, the implementation of the egalitarian attitudes represented by numerous respondents may have positive effects for Muslim women living in patriarchal societies.